A Adjustable power supply assembly and training on the physics laboratory at YPK Masehi Berastagi - Tarigan, Kerista; Timbangen, Timbangen Sembiring; Simamora, Widya; Simamora, Berto; Simatupang, Robin (Talenta Publisher, 2019)
Adjustable power supply assembly and training have been conducted to private YPK Berastagi high school students in Berastagi District, Karo. This activity was carried out in partnership with the University of North Sumatra in the form of community service. The purpose of the training and making of this study program is to improve the teaching activities of the theory and practice of the field of electronic physics to partners. The training and making of the study program were carried out using the theory understanding method, assembling and testing it. The main components and functions used are the 220V 5A step down transformer, 5A rectifier diodes as dc rectifiers, 4700 ÂµF electrolyte capacitors as filters, and IC LM 317 regulators as voltage regulators and are equipped with current amplifiers, 2SA 73 transistors and 2SC 41 Based on test and analysis data obtained by students (i), the output voltage can be adjusted from 1.27 - 24.62 volts with a maximum current of 3A. While the ripple voltage, Vr pp = 0.1 Volt. obtained mV. Based on the PS test results of assemblies against the burden of motorcycle lights, 40 Watt works well. Based on these results, the PS can be used.